Alex eaudiobook - Bennett, Sawyer (Cold Fury Hockey, 2015)
Hockey star Alexander Crossman has a reputation as a cold-hearted player on and off the ice. Pushed into the sport by his alcoholic father, Alex isn't afraid to give fans the proverbial middle finger, relishing his role as the MVP they love to hate. Management, however, isn't so amused. Now Alex has a choice: fix his public image through community service or ride the bench. But Alex refuses to be molded into the Carolina Cold Fury poster boy . . . not even by a tempting redhead with killer curves. As a social worker, Sutton Price is accustomed to difficult people like Alex, who's been assigned to help her create a drug-abuse awareness program for at-risk youth as part of the Fury's effort to clean up his image. What she doesn't expect is the arrogant smirk from his perfect lips stirring her most heated fantasies. But Sutton isn't one to cross professional boundaries—and besides, Alex doesn't do relationships . . . or does he? The more she sees behind Alex's bad-boy façade, the more Sutton craves the man she uncovers.